Menyoal Pertanggungjawaban Pidana dan Alasan Penghapus Pidana Korporasi Terhadap Tindak Pidana Korupsi dalam RKHUP - Siti Shalima Safitri; Agnes Maria Monika Setiawati; Clara Anisya Aprilinda (CV Rewang Rencang, 2021)
As a “lex generalis”, matters that are not regulated shall refer to the Bill of Indonesian Criminal Code. Whereas the stipulations within the Bill of Indonesian Criminal Code are not yet mature in manifesting corporate criminal liability. The problem raised in this thesis is on the status quo of corporate criminal liability in the Anti-Corruption Law in Article 49 and 50 of the Bill of Indonesian Criminal Code and its prospects in the future. The result of this thesis is that the formulation of Article 49 results in overlapping criminal liability, thus it is necessary to see whether there is independence in giving commands. Meanwhile, Article 50 related to criminal abolition applied to corporations cannot be equated with persons so it requires to be further formulated in detail.